Bridging the domain gap: A transferable dynamic routing enhancer for robust aerial detection under adverse weather - Yu Wan; Jie Li; Liupeng Lin; Zhaowen Lv; Zaiyan Zhang; Qiangqiang Yuan; Huanfeng Shen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

MEK inhibitor cobimetinib increases calreticulin and induces immune modulation in TNBC - Ling-Ming Tseng; Ka-Yi Lau; Ji-Lin Chen; Pei-Yi Chu; Chun-Teng Huang; Wan-Lun Wang; Yuan-Ya Chang; Jiun-I Lai; Chi-Cheng Huang; Ming-Shen Dai; Chun-Yu Liu (Journal of Molecular Medicine, 2026)
Immunogenic cell death (ICD) can activate immune cells and potentiate the response to immunotherapy. The mitogen-activated protein kinase (MAPK) signaling pathway regulates the immune response and mediates T-cell receptor signaling. Activation of the MAPK signaling pathway decreases the levels of tumor-infiltrating lymphocytes in triple-negative breast cancer (TNBC) and is associated with worse survival. Here, we investigated the potential of the MEK inhibitor cobimetinib as an ICD inducer in TNBC. We demonstrated that cobimetinib elicited hallmarks of ICD, including elevated levels of damage-associated molecular patterns. Ectopic ERK expression attenuated cobimetinib-induced CRT. Cobimetinib also evoked caspase-8 activation with increased Bax and Bak expression, while caspase inhibitor suppressed cobimetinib-induced CRT expression and apoptosis. In immunocompetent (BALB/c) mice bearing 4T1 tumors, cobimetinib exhibited stronger tumor growth inhibition than in immunodeficient (nude) mice, suggesting an immune-dependent antitumor effect. Furthermore, cobimetinib treatment increased the proportions of naïve CD8 + T cells and effector CD4 + T cells and decreases the proportion of myeloid-derived suppressor cells in immunocompetent mice bearing 4T1 tumors. Notably, we observed differential immunomodulatory effects of cobimetinib in tumor-bearing mice compared to non–tumor-bearing immunocompetent mice. Our findings indicate that MEK inhibition is associated with ICD-related molecular alterations, and that cobimetinib may contribute to immune modulation in TNBC.

Dihydrolipoamide dehydrogenase promotes hepatocellular carcinoma progression and modulates cuproptosis-dependent cell death - Mao-feng Zhong; Yu-yu Guo; Yuan Tian; Tian-xiao Zheng; Lu-yuan Zhu; Juan Du; Wan-fu Lin (Functional & Integrative Genomics, 2026)

Second-order memristor-coupled heterogeneous neuron model: multi-attractor, multi-stability, and hardware implementation - Miao Xie; Hairong Lin; Qiuzhen Wan; Fei Yu; Wei Yao (Cognitive Neurodynamics, 2026)

Size matching between laccase and carrier via tunable diamine-derived flexible spacer arms for enhanced phenolic wastewater degradation - Jie Zhang; Yiqi Gong; Zhipeng Qin; Xinyi Liu; Jiao Yu; Tao Feng; Wan Zhang; Wenjing Lin; Kaiyue Kang; Xuemei Tan; Lin Zhuo; Ruiqi Wang; et al. (Journal of Water Process Engineering, 2026)

Tailoring Cu-doped SmMn2O5 with rich Mn4+ active sites for highly efficient and selective ultra-low temperature photothermal NOx catalytic reduction - Mingxia Wu; Jiale Cheng; Yu Wang; Siying Zhang; Yi Li; Ruixue Bai; Chunming Yang; Lin Liu; Feng Fu; Jun Wan (Chemical Engineering Journal, 2026)

Molecular mechanisms of neutron irradiation damage in CL-20: A multiscale modeling approach from collision cascades to real-space defect mapping - Wei-Yi Li; Tao Wang; Rong Liu; Yu-Heng Li; Wan-Xiao Guo; Xi-Yao Yun; Yi-Lin Fang; Jin-Tao Wang; Ning Gao (Chemical Engineering Journal, 2026)

S-methoprene affected the population growth of Ephestia elutella (Hübner) - Lin-chong An; Xiao-fei Yu; Si-qi Wan; Mao-fa Yang (Journal of Stored Products Research, 2026)

FBG-based dynamic characterization of a scaled offshore wind turbine foundation model under impact and recorded seismic excitations - Jui-Chi Lin; Yi-Lun Liao; Bor-Yann Chen; I-Hsin Chiu; Wan-Yu Xu; You-Chen Liao; Yi-Heng Yang; Yu-Hsi Huang (Ocean Engineering, 2026)

An improved LC–MS/MS method for simultaneous determination of deoxynivalenol and its modified forms in grains and feed - Dongying Tian; Gang Lin; Ronghua Zhu; Alexandros Yiannikouris; Yuping Wan; Zhaoqin Wang; Yang Yu; Peilon Wang; Ruiguo Wang (Food Chemistry, 2026)

The Use of Double-tube Multiplex TaqMan Real-time RT-PCR for the Simultaneous Detection of Foodborne Viruses in Shellfish - Peng Lin; Ling Chen; Qiang Wan; Zhihe Cai; Liang Xue; Qinghua Ye; Fufeng Jiang; Xiaoying Qu; Jiahui Huang; Huishu Huang; Yu Ding; Moutong Chen; et al. (Food Control, 2026)

Design, preparation and performance study of DAP-1 based conductive energetic composite - Wan-Jun Wei; Rui Pu; Yu-Ruizhi Lin; Ying-Qi Mao; Qi-Long Yan; Shao-Li Chen (Chemical Engineering Journal, 2026)

Atomically precise ferrocene-based Fe/Mn nanocluster for solar-driven cycloaddition of epoxides with carbon dioxide - Xue-Feng He; Chun-Yang Li; Yu-Lin Jiang; Wan-Yu Zhu; Qiu-Hong Cheng; Kun Huang; Da-Bin Qin; Xiang-Yu Zhang (Chemical Engineering Journal, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Green synthesized Cu2O/TiO2 nanotube heterojunction for pharmaceutical mineralization and simultaneous hydrogen evolution: mechanistic insight and toxicity assessment - Fang-Yu Liang; Dong-Ni Wu; Wan-Chun Lin; Yi-Ching Lin; Chia-En Tsai; Chia-Hua Lin; Wu-Xing Chen; Chia-Hung Chen; Yen-Ping Peng (Journal of Environmental Management, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Revealing the impact of low-temperature fermentation by Weissella cibaria MXJSHZ8-3 on soymilk quality through volatile flavor compounds and metabolite profiles - Yanhong Lin; Guandi Chen; Zhen Liu; Yilai Wan; Jingru Zhang; Hexi Yuan; Shiyang Yu; Yang Jiang; Ming Ning; Peng Yu; Zhongkai Zhou (Food Chemistry, 2026)

Sn-2 palmitate ameliorates dyslipidemia in high-fat-fed aged mice via bile acid-mediated gut-liver-adipose cross-talk - Lin Zhu; Mingzhe Deng; Hong Zhang; Zhenbo Xu; Peijin Tong; Jianchun Wan; Boyan Gao; Liangli (Lucy) Yu; Yaqiong Zhang (Food Bioscience, 2026)

Efficient Underwater Image Super-Resolution via Learnable Color Conversion and Dual-Branch Mamba Network - Yu-Yang Lin; Wan-Jen Huang; Chia-Hung Yeh; Yi-Shiuan Yang; Chua-Chin Wang (Journal of Marine Science and Engineering, 2026)
Underwater image super-resolution plays an important role in marine exploration, as it aims to recover clearer and higher-resolution images from degraded low-resolution observations. However, in underwater environments, this task is particularly challenging due to non-uniform spectral attenuation and particle scattering. Underwater, red light fades quickly, leading to color distortion and loss of details. To address this while keeping the model lightweight, we propose a dynamic color-space network for single-image super-resolution. Traditional methods use fixed color conversion and cannot handle non-uniform attenuation well. We instead use a learnable module to adaptively obtain luminance (Y) and chrominance (CbCr) representations. Building upon this representation, we employ a highly efficient dual-branch architecture where the Y-channel features are processed using light Mamba blocks to capture spatial dependencies with linear complexity, while the CbCr-channel features are restored by a lightweight convolutional neural network. Finally, a lightweight residual model utilizing depth-wise separable convolutions (DSC), deformable convolutions, and pixel attention mechanisms is introduced to refine the features and suppress artifacts. Experimental results demonstrate that while achieving competitive restoration quality, the proposed method drastically reduces computational complexity and parameter count compared to other large-scale models. This balance between visual quality and computational efficiency makes the proposed method well-suited for real-time deployment on resource-constrained autonomous underwater vehicles (AUVs).

Tinosporoside E and tinosporane A: two new clerodane diterpenes from the tuberous roots of Paratinospora sagittata - Li Fan; Yu-Jie Zhang; Shi-Peng Zhang; Wan-Shu Li; Ling-Juan Zhu; Hang-Juan Lin (Natural Product Research, 2026)

Multi-sensor fusion for autonomous vertical docking in kilometer-scale deep-sea environments - Suohang Zhang; Lin Yu; Shipang Qian; Jiaxuan Song; Ziyang Wan; Ruiheng Liu; Lu Wang; Xinyu Fei; Canjun Yang; Yanhu Chen (Ocean Engineering, 2026)

Mechanically engineered multi-oxide heterojunctions for bifunctional antibacterial and photocatalytic environmental remediation - Juan Pei; Jialan Mi; Shuhan Yao; Mingxing Guo; Ye Zhang; Xiaoling Wan; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Haichun Zeng; et al. (Journal of Environmental Chemical Engineering, 2026)

Efficient hydrolysis of glycosides by Pichia kudriavzevii with high-activity β-glucosidase: a critical role in enhancing terpene aroma in beer - Lin Yuan; Xiaoping Hou; Yang He; Xiujuan Wan; Jiaxin Han; Wenqi Xu; Shuo Yu; Shuang Bi; Lijuan Ma; Lei Xing (Food Chemistry, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

A power-law relationship between bulk modulus and permeability in fractured sandstone: Insights from tidal analysis - Xu-Lin Tang; Xiao-Wei Jiang; Zhe-Ming Shi; Zhi-Yu Qi; De-Qiang Mao; Xu-Sheng Wang; Yan Zhang; Li Wan; Hong-Bin Yan (Engineering Geology, 2026)

Benzotriazole ultraviolet stabilizers impair trophoblast function at nanomolar concentrations via GPER signaling: implications for placental health - Ze-Pei Zhao; Shi-Ye Zhu; Ying-Huang Hu; Yu-Ke Wan; Shang-Jun Xu; Jie-Zhi Ma; Deng-Ni Lai; An-Wei Chen; Yuan Yang; Lin Luo; Lin-Ying Cao (Chemico-Biological Interactions, 2026)

Phylogeny, species diversity and divergence time of Diaporthe causing leaf blight on Acer palmatum in China - Yu Wan; De-Wei Li; Qiu-Yue Zhang; Yuan-Zhi Si; Jian-Wei Sun; Xiaolei Ding; Lin Huang; Li-Hua Zhu (Fungal Biology, 2026)

Formaldehyde activates the RUNX1–ISX axis to promote leukemic reprogramming, a pathway associated with poor prognosis in pediatric B-ALL - Pei-Chin Lin; Li-Ting Wang; Li-Heng Ye; Pin-Ying Tseng; Pei-Hsien Huang; Wan-Yi Hsu; Yu-Mei Liao; Shyh-Shin Chiou; Shih-Hsien Hsu (Environmental Pollution, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Preserving the functional integrity of BiP1 is essential for rice storage protein export from the endoplasmic reticulum - Wenkun Yang; Tian Pan; Fan Wang; Yun Zhu; Kunneng Zhou; Binglei Zhang; Gexing Wan; Yu Chen; Yu Zhang; Xiejun Sun; Cailin Lei; Jie Wang; et al. (Plant Science, 2026)

Assessing organic substitution thresholds in smallholder farms: Results from a 34-year experiment on crop—livestock integration systems - Yu Ning; Shuai-lin Li; Xin-hui Zhang; Zhu-qing Xia; Yun Gao; Lu Sun; Qiang Ma; Wan-tai Yu (European Journal of Agronomy, 2026)

Thin film nanocomposite membrane incorporated with sulfonic acid-based HOFs for efficient reverse osmosis desalination - Yu-ting Liu; Zi-yue Tang; Zi-ao Zong; Wan-zhen Wang; Xiao-yin Zhang; Xin-ping Song; Xiang-min Meng; Rijia Lin; Jingwei Hou (Desalination, 2026)

Coated ferrous sulfate requirement for alleviating hypoxia-induced hepatopancreatic inflammation in sub-adult grass carp (Ctenopharyngodon idella) - Yu-Juan Yang; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Hong-Yun Zhang; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Ying-Gu Kuang; Xiao-Qiu Zhou; Lin Feng (Fish & Shellfish Immunology, 2026)

Utilizing conjugation effect of nitrogen unshared electron to architect redox-active polymer for sodium-ion storage - Liang-Yu Wang; Shun-Yu Yao; Jing-Zhe Wan; Qi-Hang Wang; Chao Ma; Jiu-Lin Wang; Kai-Xue Wang (Chemical Engineering Journal, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

CSP-YOWO-TrajNet: A spatio-temporal detection method for laying hen heat stress behavior - Zhenwei Yu; Liyin Zhang; Liqing Wan; Hai Lin; Khurram Yousaf; Geqi Yan; Hongchao Jiao; Chaoyuan Wang; Fuyang Tian (Journal of Thermal Biology, 2026)

A bezafibrate bearing Pt(IV) prodrug triggers ferroptosis via modulating lipid metabolism in lung cancer cells - Neng Wan; Xuan-Lin Ren; Xiang-Yu Ma; Tao Zhu; Cheng-Zhi Xie; Jing-Yuan Xu; Xin Qiao (JBIC Journal of Biological Inorganic Chemistry, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Association between urinary metabolites of 1,3-butadiene and toluene exposure with kidney function indices in Taiwanese school-aged children living near a petrochemical complex - Po-Keng Cheng; Vinoth Kumar Ponnusamy; Wei-Hong Lin; Jeganathan Chinnadurai; Pei-Chien Tsai; Cai-Yu Chen; Wan-Ting Chang; Po-Chin Huang (Environmental Pollution, 2026)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Early hyperferritinemia in polytrauma: a biomarker of systemic inflammation and mortality risk in a multicenter cohort study - Shunyao Chen; Teding Chang; Jialiu Luo; Cong Zhang; Peidong Zhang; Shuaipeng Gu; Zhiqiang Lin; Yujie Chen; Youxie Shen; Liming Dong; Qian Wan; Liang He; et al. (Inflammation Research, 2025)

High-Resolution Three-Pressure Prediction of Lianggaoshan Formation in LT1 Well block of Eastern Sichuan Risk Exploration Area - Yu-wei Wang; Ke-zhen Wan; Rong-rong Zhao; Wen-hao Li; Yang Lin; Hao Long; Hu Zhao (Applied Geophysics, 2025)

Hypoglycemic cucurbitane-type triterpenoids from fruits of Citrullus colocynthis - Hua-Wei Lv; Yu Wan; Wen-Lin Fan; Meng-Di Zhu; Qiao-Liang Wang; Zhong-Bo Zhou; Chang-Chun Chen; Hong Wang; Xing-Nuo Li (Phytochemistry, 2025)

Clay sediment adhesion-dominated clogging and its recovery under infiltration washing in statically compacted pervious concrete - Yu Ding; Yapei Xia; Lin Guo; Qi Wan; Zhenyao Xia; Hai Xiao; Yunkang Rao (Journal of Hydrology, 2025)

Synergistic effects of biochar and E. coli on reducing cadmium bioavailability and improving soil fertility through enhanced bacterial-fungal interactions - Quan Chen; Rongrong Lin; Wan-Rong Zhang; Yafeng Wang; Yanqing Xiong; Pengfei Wang; Yu Huang; Min Wu; Peng Yi; Bo Pan (Journal of Hazardous Materials, 2025)

Mechanochemical synthesis of ZnO@TiO2 II heterojunction material: Photocatalytic degradation and antibacterial synergistic effect - Juan Pei; Xiaoling Wan; Mingxing Guo; Jialan Mi; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Siwei Xiang; Qianyu Zhang; Haichun Zeng; et al. (Chemical Engineering Journal, 2025)

Human adenovirus in Taiwan, 2019–2023 - Su-Lin Yang; Wan-Ju Tsai; Chung-Hao Li; Yu-Hsin Cheng; Shu-Wei Lin; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2025)

Carbon-nitrogen-phosphorus level regulation of potentially toxic elements and enzyme activities in paddy soil aggregates: Straw and organic fertilizer effects - Keqi Zhao; Wenbo Xiao; Nanyi Wang; Xiaobing Zhang; Ying Wang; Hua Peng; Jiachao Zhang; Anwei Chen; Renli Qi; Fangying Yu; Dan Wan; Lin Luo; et al. (Journal of Environmental Chemical Engineering, 2025)

A generalized chemical kinetics explains heterocyclic amine formation in high-temperature processed meats - Kuen-Yuh Wu; Yu-Hsuan Kuo; Pei-Chen Chao; Yu-Syuan Luo; Wan-Yu Lin; Su-Yin Chiang (Food Chemistry, 2025)

A ratiometric fluorescence probe based on curcumin and supramolecular deep eutectic solvent for in vivo imaging cerebral pH - Wan-Chun Luo; Jin-Tao Zhang; Li-Na Bao; Lin-Jiao Yang; Zi-Ke Yang; Ming Jiang; Xu Yu; Li Xu (Chemical Engineering Journal, 2025)

Ultra-long and rapid operating zinc metal batteries enabled by multifunctional polarizable interface stabilizer - Song-Lin Tian; Li Lin; Si-Yu Jiang; Li-Na Song; Hai-Rui Wang; Ping Nie; Li-Min Chang; Wan-Qiang Liu (Chemical Engineering Journal, 2025)

Integrated core-shell structured dual-mode thermoresponsive optical-electrical sensing fiber for accurate temperature recognition and early fire warning - Hualing He; Jie Xu; Md Hasib Mia; Zhonghe Yu; Yuhang Wan; Qing Jiang; Xueru Qu; Jinru Liu; Lin Hou; Yueyue Song; Zhicai Yu (Chemical Engineering Journal, 2025)

Self-reconstructed Cu2O/Co3O4@NC heterostructured catalyst for efficient tandem electrocatalytic conversion of nitrate to ammonia - Lin Zhu Dai; Guo Yu Yong; Wan Ni Gan; Ting Li; Zhi Cheng Chen; Lun Yao Pan; Hong Qun Luo; Nian Bing Li (Chemical Engineering Journal, 2025)

Senegenin ameliorates diabetic encephalopathy via promoting mitophagy and repressing NLRP3 inflammasome activation - Xiao-dan Yan; Yu Yang; Wan-ting Zhang; Qing-quan Kong; Xi-tong Zheng; Lin-sen Li; Qing Yu (Psychopharmacology, 2025)

The Antimicrobial Peptide Tilapia Piscidin 4 Induced the Apoptosis of Bladder Cancer Through ERK/SIRT1/PGC-1α Signaling Pathway - Chun-Feng Chang; Po-Chih Chang; Yi-Chen Lee; Chieh-Yu Pan; Hui-Min Chang; Wan-Ju Wu; Mei-Ying Lin; Chung-Yi Chen; Zhi-Hong Wen; Chien-Hsing Lee (Probiotics and Antimicrobial Proteins, 2025)

Upregulation of PD-1 on Peripheral T cells Subsets is Associated with Parkinson's Disease - Zhi-Ling Zhang; Pang-Hai Ye; Wei-Xin Kong; Jin Li; Si Zhu; Yu-Wan Lin; Ping-Yi Xu; Wen-Yuan Guo (Molecular Neurobiology, 2025)

Development and application of InDels and SNPs markers based on whole-genome resequencing in Chinese cabbage - Kai-Wen Liu; Wan-Jie Men; Jin-Xia Feng; Iqbal Hussain; Hui Sheng; Li-Wei Zhang; Zhong-Ren Dai; Hai-Jiang Hu; Jian-Hao Yang; Na Lei; Xiao-Lin Yu (Horticulture, Environment, and Biotechnology, 2025)

New perspective on mechanism of L-arginine in promoting skeletal muscle growth of grass carp (Ctenopharyngodon Idella): Via enhancing skeletal muscle functions and regulating energy metabolism - Qiu-Yan Chen; Yu-Long Ma; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2025)

Integrating machine learning and metabolomics to uncover new biomarkers for predicting pesticide exposure among patients with kidney function decline - Junne-Ming Sung; Yu-Chi Hung; Wan-Ru Wang; Chiau-Jun Chu; Yen-Ping Lin; Kuan-Hung Liu; Trias Mahmudiono; Hsiu-Ling Chen (Science of The Total Environment, 2025)

Reducing environment and enhanced productivity controlled the accumulation of organic matter in the Upper Yangtze Basin, South China during the Late Ordovician-Early Silurian - Yan-Jun Bao; Yuan-Yuan Sun; Di Zhang; Jian-Fei Yan; Yu-Peng Men; Wei Sun; Jia-Shan Lin; You-Li Wan; Jian-Wei Kang; Wen-Hua Wang; Qiangba Zhaxi (Journal of Asian Earth Sciences, 2025)

Navigating crowds: Reconsidering visitor recreational experience and crowding preference for a forest park in Taiwan - Wan-Yu Liu; Chin-Chun Yen; Rachel S.K. Lee; Chun-Cheng Lin (Forest Policy and Economics, 2025)

Identification of a dominant stripe rust resistance gene YrXY on chromosome 6R in hexaploid triticale - Yu Lin; Yahan Yang; Yichang Gou; Zhenzhen Xue; Genxi Huang; Hongshen Wan; Zhiqiang Wang; Lin Huang; Houyang Kang; Yi Wang; Yonghong Zhou; Haiqin Zhang (Theoretical and Applied Genetics, 2025)

Tremella fuciformis Polysaccharides Alleviate Early Brain Injury in Experimental Subarachnoid Hemorrhage by Inhibiting the KDR-Mediated P38 MAPK/NF-κB Pathway - Yu-hui Wan; Zeng-jing Cheng; Ling-xiang Fan; De-hong Yang; Bing-lin Chen; Xiang-xin Chen; Qing Zhu (Molecular Neurobiology, 2025)

CCN1 Is a Therapeutic Target for Reperfused Ischemic Brain Injury - Gilbert Aaron Lee; Yu-Wei Chang; Jing-Huei Lai; Tzu-Hao Chang; Shiu-Wen Huang; Chih‑Hao Yang; Ting-An Shen; Wan-Li Lin; Ying-Chieh Wu; Li-Wen Tseng; Sung-Hui Tseng; Yung-Chieh Chen; et al. (Translational Stroke Research, 2025)

Lactiplantibacillus plantarum GMNL-661 Ameliorates Clostridioides difficile Infection and Reconfigures Intestinal Microbiota in a Murine Model - Meng-Jia Li; Hong-Ming Chen; Yueh-Lin Chen; Yi-Hsin Lai; Cheng-Yu Lai; Jhen-Wei Ruan; Jenn-Wei Chen; Wan-Hua Tsai; Wen-Chien Ko; Pei-Jane Tsai (Probiotics and Antimicrobial Proteins, 2025)

Rapid evaluation of Curcuma origin and quality based on E-eye, flash GC e-nose, and FT-NIR combined with machine learning technologies - Qiang Guo; Ming-xuan Li; Rao Fu; Xin Wan; Wen-hao Dong; Chun-qin Mao; Zhen-hua Bian; De Ji; Tu-lin Lu; Yu Li (Food Chemistry, 2025)

Infrared Laser Stimulation of Purkinje Cells Primarily Depends on TRP Channel Activation - Bin-Bin Dong; Chen Wang; Wan-Qi Huang; Yu-Peng Bian; Jun Liu; Wei Chen; Lin Zhou; Ying Shen; Luxi Wang (Neuroscience Bulletin, 2025)

Untargeted metabolomics and network pharmacology reveal the uric acid-lowering effects of alcohol extract of Gnaphalium affine and its extracts in hyperuricemic rats - Chen Wang; Xinchao He; Lijuan Rao; Jiajing Liao; Jin Qian; Xuefeng Yu; Sen Mei; Suqin Lin; Linqian Xu; Guiming Fu; Yin Wan (Food Bioscience, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Boosted catalytic soot oxidation by hierarchical hollow cobalt oxide constructed from a Template-Sacrificial Method: Promoting Roles of morphologies and oxygen vacancies - Yu-Chih Tsai; Mei-Chen Wan; Shen Yan Lin; Vo Thi Thanh Thuy; Nguyen Nhat Huy; Duong Dinh Tuan; Jechan Lee; Kun-Yi Andrew Lin (Chemical Engineering Journal, 2025)

Perylene diimide cathode interface layer with siloxane bay-modification for efficient and stable organic solar cells - Dan Zhou; Yujie Pu; Yanyan Wang; Lin Hu; Jianwei Quan; Senmei Lan; Jiangang Ma; Fang Wang; Wentian Wan; Yongfen Tong; Ruizhi Lv; Haitao Xu; et al. (Chemical Engineering Journal, 2025)

Polyploid crape myrtle was produced through hybridizing with 2n gametes induced by high-temperature - Yu Xu; Qi Hu; Qifang Lin; Xiufeng Chi; Ping Shen; Xin Wang; Zhiting Wan; Xinwei Jiang; Jia Wang; Tangren Cheng; Qixiang Zhang; Huitang Pan (Euphytica, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Associations between lifestyle factors, physiological conditions, and epigenetic age acceleration in an Asian population - Yu-Ru Wu; Wan-Yu Lin (Biogerontology, 2025)
Epigenetic clocks use DNA methylation (DNAm) levels to predict an individual’s biological age. However, relationships between lifestyle/biomarkers and epigenetic age acceleration (EAA) in Asian populations remain unknown. We here explored associations between lifestyle factors, physiological conditions, and epigenetic markers, including HannumEAA, IEAA, PhenoEAA, GrimEAA, DunedinPACE, DNAm-based smoking pack-years (DNAmPACKYRS), and DNAm plasminogen activator inhibitor 1 level (DNAmPAI1). A total of 2474 Taiwan Biobank (TWB) individuals aged between 30 and 70 provided physical health examinations, lifestyle questionnaire surveys, and blood and urine samples. Partial correlation analysis (while adjusting for chronological age, smoking, and drinking status) demonstrated that 29 factors were significantly correlated with at least one epigenetic marker (Pearson’s correlation coefficient | r |> 0.15). Subsequently, by exploring the model with the smallest Akaike information criterion (AIC), we identified the best model for each epigenetic marker. As a DNAm-based marker demonstrated to predict healthspan and lifespan with greater accuracy, GrimEAA was also found to be better explained by lifestyle factors and physiological conditions. Totally 15 factors explained 44.7% variability in GrimEAA, including sex, body mass index (BMI), waist-hip ratio (WHR), smoking, hemoglobin A1c (HbA1c), high-density lipoprotein cholesterol (HDL-C), creatinine, uric acid, gamma-glutamyl transferase (GGT), hemoglobin, and five cell-type proportions. In summary, smoking, elevated HbA1c, BMI, WHR, GGT, and uric acid were associated with more than one kind of EAA. At the same time, higher HDL-C and hemoglobin were related to epigenetic age deceleration (EAD). These findings offer valuable insights into biological aging.

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Aggregative Infestation of Nine Bostrichidae Species on the Madagascar Almond Tree, Terminalia neotaliala Capuron (Myrtales: Combretaceae) - Xiao-Lu Cao; Li Yu; Jian-Song Wei; Qiu-Hong Tao; Qian Lu; Wan-Xuan Wei; Xia-Lin Zheng (Neotropical Entomology, 2025)

Identification and characterization of Alternaria spp. causing leaf blotch on Salix matsudana: A study from Rudong city, China - Yi-Lin Chen; Bing-Yao Peng; Yu Wan; De-Wei Li; Li-Hua Zhu (Crop Protection, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Uncovering characteristic and enantiomeric distribution of volatile components in Huangshan Maofeng and Zhejiang baked green teas - Yu-Hui Zhang; Pan-Deng Lei; Yong Ding; Xiao-Ting Zhai; Xiao-Chun Wan; Wei-Xuan Li; Yue Zhang; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Chemistry, 2025)

MEHP induced mitochondrial damage by promoting ROS production in CIK cells, leading to apoptosis, autophagy, cell cycle arrest - Lu Li; Wan Li; Yufeng Liu; Bing Han; Yanbo Yu; Hongjin Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

OsPAD1, encoding a non-specific lipid transfer protein, is required for rice pollen aperture formation - Qiming Wang; Yunlu Tian; Keyi Chen; Shanshan Zhu; Yehui Xiong; Chaolong Wang; Xiaowen Yu; Wenting Bai; Hai Zheng; Shimin You; Yang Hu; Dekun Lei; et al. (Plant Molecular Biology, 2025)

Knocking Down HN1 Blocks Helicobacter pylori-Induced Malignant Phenotypes in Gastric Mucosal Cells and Inhibits Gastric Cancer Cell Proliferation, Cytoskeleton Remodeling, and Migration - Ying Huang; Xiaofei Wang; Hao Liu; Xiangkun Meng; Hua Yin; Ruirui Hou; Wan Lin; Xu Zhang; Jun Ma; Xiaoxu Zhang; Feixiong Zhang; Yu Miao (Biochemical Genetics, 2025)

Dual-CycleGANs with Dynamic Guidance for Robust Underwater Image Restoration - Yu-Yang Lin; Wan-Jen Huang; Chia-Hung Yeh (Journal of Marine Science and Engineering, 2025)
The field of underwater image processing has gained significant attention recently, offering great potential for enhanced exploration of underwater environments, including applications such as underwater terrain scanning and autonomous underwater vehicles. However, underwater images frequently face challenges such as light attenuation, color distortion, and noise introduced by artificial light sources. These degradations not only affect image quality but also hinder the effectiveness of related application tasks. To address these issues, this paper presents a novel deep network model for single under-water image restoration. Our model does not rely on paired training images and incorporates two cycle-consistent generative adversarial network (CycleGAN) structures, forming a dual-CycleGAN architecture. This enables the simultaneous conversion of an underwater image to its in-air (atmospheric) counterpart while learning a light field image to guide the underwater image towards its in-air version. Experimental results indicate that the proposed method provides superior (or at least comparable) image restoration performance, both in terms of quantitative measures and visual quality, when compared to existing state-of-the-art techniques. Our model significantly reduces computational complexity, resulting in a more efficient approach that maintains superior restoration capabilities, ensuring faster processing times and lower memory usage, making it highly suitable for real-world applications.

Enhancing indoor air quality and cardiopulmonary health in patients with asthma by photocatalytic oxidation and filters air cleaner - Jia Lin Zhang; Guan-Yu Liao; Hong-Yi Lin; Jie-An Xie; Wan-Chen Li; Huang-Chi Chen; Da Wei Wu; Huai-Lei Juan; Jia-Yu Kuo; Pei-Shih Chen (Journal of Hazardous Materials, 2025)

The obesity-related mutation gene on nonalcoholic fatty liver disease - Yen-Yu Chen; Chi-Sheng Chen; Jee-Fu Huang; Wen-Hsiu Su; Chia-Yang Li; Wei-Shiun Chen; En-Sheng Lin; Wan-Long Chuang; Ming-Lung Yu; Shu-Chi Wang (Human Genetics, 2025)

Association of PM2.5 exposure in early pregnancy and maternal liver function: A retrospective cohort study in Shenzhen, China - Zhijian Chen; Minting Zhu; Weigui Ni; Bo Wu; Tao Liu; Bingyi Lin; Lijuan Lai; Yi Jing; Long Jiang; Zhongai Ouyang; Jianxiong Hu; Haoqu Zheng; et al. (Environmental Research, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Insufficient FUNDC1-dependent mitophagy due to early environmental cadmium exposure triggers mitochondrial redox imbalance to aggravate diet-induced lipotoxicity - Cai-Yu Lian; Hui-Jia Li; Wei-Hao Xia; Yue Li; Xue-Lei Zhou; Du-Bao Yang; Xue-Mei Wan; Lin Wang (Environmental Pollution, 2024)

The role of aroA and ppk1 in Aeromonas veronii pathogenicity and the efficacy evaluation of mutant strain AV-ΔaroA/ppk1 as a live attenuated vaccine - Jiahui Lu; Wan'e Ding; Jinming Wei; Hua Ye; Hui Luo; Yun Li; Ying Lin; Yongyao Yu; Jiayun Yao; Ronghua Wu (Fish & Shellfish Immunology, 2024)

Positively charged loose nanofiltration membranes via the assembly of amino-quinone networks for efficient dye/salt separation - Tian Gao; Ping Fu; Wan-Long Li; Wan-Ting Lin; Yuan-Hui Yu; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2024)

Sex-Specific Associations of Five Serum Essential Metal Elements with Thyroid Nodules in Euthyroid Adults: a Cross‑sectional Study - Qintao Ma; Ying Li; Genfeng Yu; Siyang Liu; Yuqi Jiang; Hualin Duan; Dongmei Wang; Yajun He; Xingying Chen; Nanfang Yao; Xu Lin; Heng Wan; et al. (Biological Trace Element Research, 2024)

Verification of Seasonal Prediction by the Upgraded China Multi-Model Ensemble Prediction System (CMMEv2.0) - Jie Wu; Hong-Li Ren; Jianghua Wan; Jingpeng Liu; Jinqing Zuo; Changzheng Liu; Ying Liu; Yu Nie; Chongbo Zhao; Li Guo; Bo Lu; Lijuan Chen; et al. (Journal of Meteorological Research, 2024)

DEM-CFD coupling simulation and optimisation of rice seed particles seeding a hill in double cavity pneumatic seed metering device - He Xing; Xiaoman Cao; Peng Zhong; Yikai Wan; Junjiang Lin; Yu Zang; Guozhong Zhang (Computers and Electronics in Agriculture, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

Emamectin benzoate exposure induced carp kidney injury by triggering mitochondrial oxidative stress to accelerate ferroptosis and autophagy - Lu Li; Wan Li; Yufeng Liu; Bing Han; Yanbo Yu; Hongjin Lin (Pesticide Biochemistry and Physiology, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Repeated Ketamine Anesthesia during the Neonatal Period Impairs Hippocampal Neurogenesis and Long-Term Neurocognitive Function by Inhibiting Mfn2-Mediated Mitochondrial Fusion in Neural Stem Cells - He Huang; Ning Wang; Jia-Tao Lin; Yong-Kang Qiu; Wei-Feng Wu; Qiang Liu; Chen Chen; Hai-Bi Wang; Yan-Ping Liu; Wei Dong; Jie Wan; Hui Zheng; et al. (Molecular Neurobiology, 2024)

Caspase-12 is Expressed in Purkinje Neurons and Prevents Psychiatric-Like Behavior in Mice - Lin-Yan Huang; Yi-Ning Liu; Jie Chen; Hai-Xue Zhu; Li-Li Li; Zhi-Yan Liang; Jin-Xiu Song; Yu-Jie Li; Zhao-Li Hu; Dieter Demon; Andy Wullaert; Wan Wang; et al. (Molecular Neurobiology, 2024)

Norditerpenoid alkaloids from Aconitum refractum var. circinatum as autophagy inducers - Mei-Zhen Ye; Zhen-Ling Wan; Hong-Yu Ruan; Yu-Qi Yang; Ying Chen; Lin Chen; Shuai Huang; Xian-Li Zhou (Phytochemistry, 2024)

A new species of Populus and the extensive hybrid speciation arising from it on the Qinghai-Tibet Plateau - Yu-Jie Shi; Jia-Xuan Mi; Jin-Liang Huang; Fei-Fei Tian; Fang He; Yu Zhong; Han-Bo Yang; Fang Wang; Yu Xiao; Lin-Kai Yang; Fan Zhang; Liang-Hua Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

Dynamic changes and the effects of key procedures on the characteristic aroma compounds of Lu’an Guapian green tea during the manufacturing process - Jieyao Yu; Jingzhe Li; Zhi Lin; Yin Zhu; Zhihui Feng; Dejiang Ni; Shengchun Zeng; Xuehong Zeng; Yijun Wang; Jingming Ning; Liang Zhang; Xiaochun Wan; et al. (Food Research International, 2024)

Electrospun multi-functional medicated tri-section Janus nanofibers for an improved anti-adhesion tendon repair - Lin Xu; Qisheng Li; Haibing Wang; Hui Liu; Deng-Guang Yu; Sim-Wan Annie Bligh; Xuhua Lu (Chemical Engineering Journal, 2024)

Sunlight enhanced the formation of tribromomethane from benzotriazole degradation during the sunlight/free chlorine treatment in the presence of bromide - Ming-Chi Hsieh; Wan-Ning Lee; Yi-Hsuan Chu; Hank Hui-Hsiang Lin; Angela Yu-Chen Lin (Chemosphere, 2024)

In vivo study on osteogenic efficiency of nHA/ gel porous scaffold with nacre water-soluble matrix - SiRi-GuLeng Li; Zhu-Ling Guo; Si-Yu Tao; Tao Han; Jie Zhou; Wan-Yun Lin; Xiang Guo; Chu-Xing Li; Sunchuri Diwas; Xiao-Wen Hu (Tissue and Cell, 2024)

Therapy of liver fibrosis: From conventional approaches to nanomaterials delivery systems - Lin Chen; Yu Duan; Tingting Jiang; Chun Mao; Xinhua Zhu; Mimi Wan (Science Bulletin, 2024)

A comprehensive study combing experiment and CFD simulation on the fume hood performance for nanoparticles and isopropanol control - Guan-Yu Lin; Yi-Ming Lee; Bo-Wen Chiu; Hsuan-Yu Hsu; Chuen-Wan Chen; Chuen-Jinn Tsai (Process Safety and Environmental Protection, 2024)

Losing Tidal Flats at the Midpoint of the East Asian-Australasian Flyway over the past 100 Years - Wan-Jyun Chen; An-Yu Chang; Chia-Chi Lin; Ruey-Shing Lin; Da-Li Lin; Pei-Fen Lee (Wetlands, 2024)
The ecosystem services and functions of tidal flats have been overlooked for many decades, and tidal flat loss has been identified as a serious threat to many taxa in recent years, especially for migratory waterbirds. Despite the understanding of tidal flats change on the global scale, there are still a lot of unknowns on the small scale, including tidal flats in Taiwan, which are important stopover sites for migratory waterbirds along the East Asian–Australasian Flyway. Therefore, we collated historic topographic maps, Landsat Archive images between the 1920s and the 2020s to determine the trajectories of tidal flat change along the coastline of Taiwan. Our results show that tidal flat coverage expanded between the 1920s and the 1950s, but lost approximately 266 km 2 (58%) between the 1950s and the 2010s. The status of the tidal flats along the western coastline of Taiwan has been identified as “Endangered” based on the criteria of the IUCN Red List of Ecosystems. According to the aims of the Global Biodiversity Framework, we suggest rethinking the land use plans along the coastline to mitigate the tidal flat loss, especially the controversial issues concerning the expansion of green energy infrastructure. To realize the Nature Positive goals by 2030, recovering and restoring the tidal flat ecosystem could be one of the key strategies.

Environmental Flow Increases The Riparian Vegetation Diversity And Community Similarity - Min Guo; Wan-Lai Xue; Chen Wang; Wen-Zhong Li; He Gao; Neil Saintilan; Cheng-Lin Li; Geng Huang; Yu-Yu Wang (Wetlands, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

PARP-2 mediates cardiomyocyte aging and damage induced by doxorubicin through SIRT1 Inhibition - Chaoming Huang; Xuan Zhang; Shulin Wang; Ao Shen; Tianfen Xu; Yanhong Hou; Shuhan Gao; Yongwan Xie; Yi Zeng; Jiayu Chen; Runxiang Lin; Yu Zhang; et al. (Apoptosis, 2024)

Remediation of cadmium-contaminated soil using modified activated carbon fiber combined with electrodynamic remediation technology - Dao-lin Zhou; Yue Cheng; Yu-shan Wan (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)

3D-printed Al2O3 framework supported carbon-bridged tri-s-triazine of g-C3N4 for photocatalytic tetracycline oxidation - Chechia Hu; Lee-Lee Chang; Wei Chen; Wan-Yuan Hsu; Szu-Chia Chien; Chien-Hua Chen; Yu-Ting Lin; Tzu-Jung Hsu; Kuo-Lun Tung (Chemical Engineering Journal, 2024)

Highly water-soluble and biocompatible hyaluronic acid functionalized upconversion nanoparticles as ratiometric nanoprobes for label-free detection of nitrofuran and doxorubicin - Abdur Raheem Aleem; Rihui Chen; Tonghua Wan; Wei Song; Chuyan Wu; Xue Qiu; Qiuqiang Zhan; Kuncheng Xu; Xin Gao; Tianci Dong; Xiang Chen; Lin Yu; et al. (Food Chemistry, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Enhancing urban climate resilience: A holistic evaluation of urban forest disservices in the aftermath of typhoons - Wan-Yu Liu; Chen-Rui Liu; Chun-Cheng Lin (Urban Climate, 2024)

Identifying the source and fate of boron in geothermal water: Evidence from B/Na and B isotopes - Ying Tan; Xiao-Wei Jiang; Tao-Tao Ji; Yin-Fei Luo; Wan Dai; Hong Zhang; Zhao-Xuan Niu; Yu-De Lei; Zhi-Yuan Zhang; Tian-Yi Lin; Hua-Ming Guo (Science of The Total Environment, 2024)

Unraveling metabolic fate of a veterinary antibiotic thiamphenicol via the multi-omic approach - Jiayu Zhang; Fangliang Guo; Hebin Liang; Ke Yu; Wan Cai; Lin Lin; Xiaoyan Li; Bing Li (Chemical Engineering Journal, 2024)

High resolution osteoclast-targeted imaging-guided osteoporosis alleviation via persistent luminescence nanocomposite - Xiao Lin; Kewen Zhang; Yang Li; Fang Nan; Jun Li; Hui Zhang; Wei Deng; Weihang Ding; Kaixuan Li; Nur Jarhen; Yitong Zhou; Xiao Yu; et al. (Chemical Engineering Journal, 2024)

Microbiota-mediated metabolic perturbations in the gut and brain of mice after microplastic exposure - Sheng-Han Lee; Wan-Yu Lin; Tsun-Jen Cheng (Chemosphere, 2024)

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

A predictive model incorporating geomorphic factors for assessing the longevity of landslide-dammed lakes - Shao-Wei Wu; Wan-Yu Chan; Chao-Yuan Lin (Landslides, 2024)

Impact of Pacific–Japan pattern on temperature and heatwave events in summer over Taiwan - Wan‐Ling Tseng; Szu‐Ying Lin; Yi‐Chi Wang; Shih‐How Lo; Min‐Hui Lo; Shih‐Yu Lee; Chieh‐Ting Tsai; Huang‐Hsiung Hsu (International Journal of Climatology, 2023)
The prediction of heatwave events is vital to provide information on possible hazards caused by extremely high temperature. The Pacific–Japan (PJ) pattern is a significant climate variability that controls the summer climate over East Asia. Previous studies have reported that the meridional propagating wave structure associated with the PJ pattern can modulate summer temperature and heatwave characteristics over northeast Asian countries, such as Korea and Japan. Nevertheless, its impacts on the subtropical regions, including Taiwan, a mountainous subtropical island with an approximate population of 24 million, is not yet fully understood. In this study, we investigate the impacts of the PJ pattern on the summer temperature and heatwave characteristics in Taiwan on the interannual timescale using long‐term station‐based temperature and rainfall dataset. We found an island‐wide increase in temperature during the positive phase of the PJ pattern, which is characterized by an anticyclonic anomalous circulation over Taiwan. Meanwhile, the averaged effective area and frequency of heatwave extremes over Taiwan have increased significantly, indicating an increase of exposure to heatwaves. Our examinations of large‐scale environment suggest that the adiabatic warming due to subsidence anomaly associated with the anticyclone over Taiwan is primary contributor of surface warming, which is balanced by diabatic cooling and meridional advective cooling on a seasonal timescale. Our study consolidated the links between the PJ pattern as a climate driver, hot summers and increased summer heatwave events over Taiwan. By combining with the seasonal prediction systems and early warning systems, such understanding can help sectors that are vulnerable to heat stress to prepare for potential hazards.

Thickness-variation-insensitive near-infrared quantum dot LEDs - Wan-Shan Shen; Yang Liu; Luke Grater; So Min Park; Haoyue Wan; Yan-Jun Yu; Jia-Lin Pan; Fan-Cheng Kong; Qi-Sheng Tian; Dong-Ying Zhou; Zeke Liu; Wanli Ma; et al. (Science Bulletin, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Associations between paraben exposure, thyroid capacity, homeostasis and pituitary thyrotropic function in the general Taiwanese: Taiwan Environmental Survey for Toxicants (TEST) 2013 - Po-Chin Huang; Hsin-Chang Chen; Shih-Hao Leung; Yu-Jung Lin; Han-Bin Huang; Wan-Ting Chang; Hsin-I. Huang; Jung-Wei Chang (Environmental Science and Pollution Research, 2023)

Zero-valent iron-peroxydisulfate as synergistic co-milling agents for enhanced mechanochemical destruction of 2,4-dichlorophenol: Coupling reduction with oxidation - Ludi Song; Lvren Lin; Wenjia Wei; Shengkun Zhang; Lei Wan; Zimo Lou; Jianming Yu; Xinhua Xu (Journal of Environmental Management, 2023)

TBBPA and lead co-exposure induces grass carp liver cells apoptosis via ROS/JAK2/STAT3 signaling axis - Lu Li; Wan Li; Yufeng Liu; Xin Jin; Yanbo Yu; Hongjin Lin (Fish & Shellfish Immunology, 2023)

Fabrication of diamond/copper composite thin plate based on a single-layer close packed diamond particles network for heat dissipation - Jia-wan Peng; Feng-lin Zhang; Yu-mei Zhou; Ling-kang Xiong; Yao-jie Huang; Hong-qun Tang (Chemical Engineering Journal, 2023)

Thermally activated delayed fluorescence emitters with bulky four-coordinate boron acceptors for high-performance solution-processed OLEDs - Bowen Li; Zhenming Ding; Zhimin Wu; Meihua Liu; Shaofeng Chen; Dongcheng Chen; Zhigao Li; Long Sang; Yu Liu; Lili Lin; Weiguo Zhu; Xiaobo Wan (Chemical Engineering Journal, 2023)

Insights into the surface Structure-Sensitive photocatalytic oxidation of gaseous toluene on Pd/TiO2 catalysts - Cong Wu; Qinglong Liu; Yu Zhan; Wei Tan; Xiaoqian Wei; Qing Tong; Haiqin Wan; Lin Dong (Chemical Engineering Journal, 2023)

Dual application of Tribonema sp. GXU-A10 for purifying molasses vinasse and promoting the growth and health of Oreochromis niloticus - Hong-Yu Deng; Yue-Xin Sun; Xin-Qiang Chen; Yu Jiang; Wan-Lin Gu; Luo-Dong Huang; Pei-Hong Shen (Algal Research, 2023)

Reduction of pesticides and bacteria on Napa cabbage by ozone microbubble water - Hsiu-Ling Chen; Rachelle D. Arcega; Pei-Yu Liao; Chih-Yao Hou; Wen-Chun Liu; Yun-Ru Chen; Jong-Shinn Wu; Wan-Ru Wang; Chia-Min Lin (Postharvest Biology and Technology, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Orientin regulates the proliferation and migration of hepatocellular carcinoma cells - Jia-Yi Tao; Jing Li; Lu Wan; Bi-Zhen Dong; Yong-Jie Yu; Ye-Mao Liu; Mao-Lin Yi; Li-Peng Wan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Research on stability and control strategies for a spring-loaded valve with bypass outlet - Jie Jian; Zhi-Jun Shuai; Jia-Xuan He; Chang-Lin Meng; Tao Yu; Xi Wang; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Annals of Nuclear Energy, 2023)

MSGNet: multi-source guidance network for fish segmentation in underwater videos - Peng Zhang; Hong Yu; Haiqing Li; Xin Zhang; Sixue Wei; Wan Tu; Zongyi Yang; Junfeng Wu; Yuanshan Lin (Frontiers in Marine Science, 2023)
Fish segmentation in underwater videos provides basic data for fish measurements, which is vital information that supports fish habitat monitoring and fishery resources survey. However, because of water turbidity and insufficient lighting, fish segmentation in underwater videos has low accuracy and poor robustness. Most previous work has utilized static fish appearance information while ignoring fish motion in underwater videos. Considering that motion contains more detail, this paper proposes a method that simultaneously combines appearance and motion information to guide fish segmentation in underwater videos. First, underwater videos are preprocessed to highlight fish in motion, and obtain high-quality underwater optical flow. Then, a multi-source guidance network (MSGNet) is presented to segment fish in complex underwater videos with degraded visual features. To enhance both fish appearance and motion information, a non-local-based multiple co-attention guidance module (M-CAGM) is applied in the encoder stage, in which the appearance and motion features from the intra-frame salient fish and the moving fish in video sequences are reciprocally enhanced. In addition, a feature adaptive fusion module (FAFM) is introduced in the decoder stage to avoid errors accumulated in the video sequences due to blurred fish or inaccurate optical flow. Experiments based on three publicly available datasets were designed to test the performance of the proposed model. The mean pixel accuracy ( mPA ) and mean intersection over union ( mIoU ) of MSGNet were 91.89% and 88.91% respectively with the mixed dataset. Compared with those of the advanced underwater fish segmentation and video object segmentation models, the mPA and mIoU of the proposed model significantly improved. The results showed that MSGNet achieves excellent segmentation performance in complex underwater videos and can provide an effective segmentation solution for fisheries resource assessment and ocean observation. The proposed model and code are exposed via Github 1 .

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

The sustainable treatment of chemical polishing wastewater under low-carbon economy: Pollutants removal, resource recovery and energy generation - Cong Ding; Meng-yu Liu; Si-zhuo Wan; Zhao-yang Cai; Lin-jiang Yuan; Ru Wang; Ping Zheng (Journal of Cleaner Production, 2023)

Effects of winemaking techniques on the phenolics, organic acids, and volatile compounds of Muscat wines - Yan-lun Ju; Xue-lei Xu; Yi-ke Yu; Meng Liu; Wan-ni Wang; Jin-ren Wu; Bo-chen Liu; Yang Zhang; Yu-lin Fang (Food Bioscience, 2023)

Hierarchical CoMn-LDH based photothermal membrane with low evaporation enthalpy and narrow bandgap toward highly efficient Solar-Driven evaporation - Ruoxuan Zheng; Tong Lin; Wan-Lei Zhao; Rutao Yin; Hongqiang Li; Zhuoqun Deng; Wei Chen; Yu-Fei Song (Chemical Engineering Journal, 2023)

Regulating energy gap in Ir-based ionic complexes to generate near-infrared emissions: Application in solid-state light-emitting electrochemical cells - Yan-Ding Lin; Pei-Wan Hsiao; Wun-Yu Chen; Sih-Yu Wu; Wei-Min Zhang; Chin-Wei Lu; Hai-Ching Su (Chemical Engineering Journal, 2023)

Assessing Carbon Abatement Costs Considering Forest Carbon Sequestration and Carbon Offset Mechanism: Evidence from Taiwan - Wan-Yu Liu; Yi-Hsin Lu; Chun-Cheng Lin (Forest Science, 2023)
Based on the Greenhouse Gas Reduction and Management Act passed in 2015 and the carbon neutral target in 2050, Taiwan will most likely follow international trends by imposing carbon taxes and establishing carbon offset markets. The positive and negative effects of carbon taxes and carbon offset markets on the economy and the environment merit further investigation. Accordingly, this study adopted a carbon emission reduction (CER) cost prediction model to assess the carbon abatement costs under three scenarios: (1) a carbon offset market exists, and forest carbon sequestration can be used as carbon offsets; (2) a carbon offset market exists, but forest carbon sequestration cannot be used as carbon offsets; and (3) a carbon offset market does not exist. Forests in Taipei (with low carbon emissions) and Kaohsiung (with high carbon emissions) were selected as research sites to explore the benefits of carbon emissions trading and forest carbon sequestration. The results show that CER costs are the lowest in scenario 1 and are the highest in scenario 3. The CER costs of Kaohsiung are higher than those of Taipei. The higher the carbon price, the greater the difference in CER costs between the two cities. Study Implications: The objective of this study was to identify the optimal policy for Taiwan to effectively slow climate change. This study showed that the opening of carbon offset markets and the use of forest carbon sequestration as carbon offsets may prompt regions to increase their forest stock to lower their emission reduction costs. However, achieving 2050 carbon neutral target by solely using forest carbon sequestration is not sufficient in Taiwan.

Remarkably efficient Pt/CeO2–Al2O3 catalyst for catalytic hydrodeiodination of monoiodoacetic acid: Synergistic effect of Al2O3 and CeO2 - Minghui Li; Wen Li; Yaning Yang; Dailiang Yu; Jingling Lin; Rui Wan; Hongjie Zhu (Chemosphere, 2023)

Numerical study on unsteady propeller exciting characteristics considering shafting whirling vibration effect - Chang-Lin Meng; Zhi-Jun Shuai; Tao Yu; Ke-Xin Ren; Jie Jian; Xi Wang; Dong-Hua Wang; Wan-You Li; Chen-Xing Jiang (Ocean Engineering, 2023)

Two generations of crustal anatexis in association with two-stage exhumation of ultrahigh-pressure metamorphic rocks in the Dabie orogen - Qiong-Xia Xia; Meng Yu; Er-Lin Zhu; Ren-Xu Chen; Wan-Cai Li; Yong-Fei Zheng; Zi-Fu Zhao; Zhao-Ya Li (Lithos, 2023)

The genetic basis of the leafy seadragon’s unique camouflage morphology and avenues for its efficient conservation derived from habitat modeling - Meng Qu; Yingyi Zhang; Zexia Gao; Zhixin Zhang; Yali Liu; Shiming Wan; Xin Wang; Haiyan Yu; Huixian Zhang; Yuhong Liu; Ralf Schneider; Axel Meyer; et al. (Science China Life Sciences, 2023)

Characteristics and provenances of rare earth elements and Nd isotopes in surface sediments of mangrove wetlands in the Jiulong River Estuary, China - Bo-sen Weng; Rui-an Wan; Rui-lian Yu; Gong-ren Hu; Yu Yan; Cheng-qi Lin; Hua-bin Huang (Environmental Science and Pollution Research, 2023)

Distribution of polycyclic aromatic hydrocarbons in indoor/outdoor window films and the indoor film/air partition of northeastern Chinese college dormitories - Yu Sun; Li-Yan Liu; Lin-Lin Lv; Xi-Xi Zhou; Yu-Yan Luo; Jin-Ze Qu; Wan-Li Ma; Zi-Feng Zhang; Li Song; Li Wang; Yi-Fan Li (Chemosphere, 2023)

A cross-sectional study of the association between heavy metals and pan-cancers associated with sex hormones in NHANES 1999–2018 - Hai-ming Cao; Ya-zhu Yang; Bao-yi Huang; Yunzhe Zhang; Yu Wu; Zi Wan; Lin Ma (Environmental Science and Pollution Research, 2023)

Assessing the ecosystem services provided by conventional and organic farmlands: A better outcome for organic farmlands? - Ching-Hua Hsieh; Hsing-Wei Lin; Wan-Yu Liu (Ecosystem Services, 2023)

Paper-based analytical device coupled with Bi-MOF: Electric field amplification and fluorescence sensing of glyphosate - Chao-Qun Wan; Yue-Hong Pang; Qiu-Yu Yang; Cheng-Lin Yang; Xiao-Fang Shen (Analytica Chimica Acta, 2023)

Spatially dual-confined metallic selenide double active centers for boosting potassium ion storage - Juan Gong; Rui Zhang; Xijun Wei; Yu Liu; Qing Luo; Qi Wan; Qiaoji Zheng; Lei Wang; Shude Liu; Dunmin Lin (Chemical Engineering Journal, 2023)

Condition optimization of iron-air fuel cell to treat phosphate-containing wastewater regarding sustainable development - Ling-ling Lai; Chao Liu; Meng-yu Liu; Si-zhuo Wan; Zhi-guo Zhao; Ru Wang; Lin-jiang Yuan (Chemosphere, 2023)

Tourists' preference for colors of forest landscapes and its implications for forest landscape planning policies - Wan-Yu Liu; Chen Tsao; Chun-Cheng Lin (Forest Policy and Economics, 2023)

A fluorescent probe based on a phenylalanine derivative is capable of sequential detection of Zn2+ and Cys/His - Qiu-Yu Yu; Chuan-Wan Wei; Xiao-Juan Wang; Shu-Qin Gao; Xin-Yi Tong; Ying-Wu Lin (JBIC Journal of Biological Inorganic Chemistry, 2023)

Using colloidal AFM probe technique and XDLVO theory to predict the transport of nanoplastics in porous media - Li-Juan Feng; Zong-Lin Shi; Jian-Lu Duan; Yi Han; Xiao-Dong Sun; Jing-Ya Ma; Xiao-Yu Liu; Huan-Xin Zhang; Ning Guo; Chao Song; Wan-Song Zong; Xian-Zheng Yuan (Chemosphere, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

Dual-site oxygen activation for enhanced photocatalytic aerobic oxidation by S-scheme Ni2P/Bi3O4Br-OVs heterojunction - Weijie Yang; Kailong Sun; Jun Wan; Yang-Ai Ma; Yu Wang; Lin Liu; Bicheng Zhu; Feng Fu (Chemical Engineering Journal, 2023)

Lightweight Flexible Polyimide-Derived Laser-Induced Graphenes for High-Performance Thermal Management Applications - Yu-Sheng Hsiao; Cai-Wan Chang-Jian; Tzu-Yen Huang; Ying-Lin Chen; Chung-Wei Huang; Jen-Hsien Huang; Nian-Jheng Wu; Shih-Chieh Hsu; Chih-Ping Chen (Chemical Engineering Journal, 2023)

Liming shifts the chemical properties and microbial community structures of peanut soils with different initial pH values - Ya Lu; Hongcui Dai; Kazem Zamanian; Qiqi Sun; Caibin Wang; Zhengfeng Wu; Yongmei Zheng; Lin Li; Shubo Wan; Tianyi Yu (Applied Soil Ecology, 2023)

Transcranial Direct-Current Stimulation Regulates MCT1-PPA-PTEN-LONP1 Signaling to Confer Neuroprotection After Rat Cerebral Ischemia–Reperfusion Injury - Xiangyi Kong; Wenjie Hu; Yu Cui; Jingchen Gao; Xujin Yao; Jinyang Ren; Tao Lin; Jiangdong Sun; Yunyi Gao; Xiaohua Li; Hui Wang; Huanting Li; et al. (Molecular Neurobiology, 2022)
Propionic acid (PPA) is a critical metabolite involved in microbial fermentation, which functions to reduce fat production, inhibit inflammation, and reduce serum cholesterol levels. The role of PPA in the context of cerebral ischemia–reperfusion (I/R) injury has yet to be clarified. Increasing evidence indicate that transcranial direct-current stimulation (tDCS) is a safe approach that confers neuroprotection in cerebral ischemia injury. Here, we show that the levels of PPA were reduced in the ischemic brain following a rat cerebral I/R injury and in the cultured rat cortical neurons after oxygen–glucose deprivation (OGD), an in vitro model of ischemic injury. We found that the decreased levels of transporter protein monocarboxylate transporter-1 (MCT1) were responsible for the OGD-induced reduction of PPA. Supplementing PPA reduced ischemia-induced neuronal death after I/R. Moreover, our results revealed that the neuroprotective effect of PPA is mediated through downregulation of phosphatase PTEN and subsequent upregulation of Lon protease 1 (LONP1). We demonstrated that direct-current stimulation (DCS) increased MCT1 expression and PPA level in OGD-insulted neurons, while tDCS decreased the brain infarct volume in the MCAO rats via increasing the levels of MCT1 expression and PPA. This study supports a potential application of tDCS in ischemic stroke.

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Associations of metal profiles in blood with thyroiditis: a cross-sectional study - Yaosheng Luo; Huixian Zeng; Yanshi Ye; Genfeng Yu; Cheng Song; Siyang Liu; Xingying Chen; Yuqi Jiang; Hualin Duan; Yue Li; Shengqing He; Zhi Chen; et al. (Environmental Science and Pollution Research, 2022)
Autoimmune thyroiditis (AIT) is increasingly common, and serological markers include thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb). To determine if selected metals influence thyroiditis antibody positivity, this cross-sectional study investigated associations between metals and thyroiditis antibody status. Healthy individuals ( n = 1104) completed a questionnaire and underwent checkups of anthropometric parameters, thyroid function status, and levels of seven metals in blood (magnesium, iron, calcium, copper, zinc, manganese, and lead). Associated profiles of glyco- and lipid metabolism were also established. Logistic regression and restricted cubic spline (RCS) regression analysis were applied to adjudge associations between metals and TPOAb and TgAb status. It was found that, after adjusting for likely cofounding factors, participants with antibody positivity had significantly lower serum concentrations of magnesium and iron. When serum magnesium levels were analyzed in quartiles, the odds ratios of quartile 4 were 0.329–fold (95% confidence interval (CI): 0.167–0647) and 0.259-fold (95% CI 0.177–0.574) that of quartile 1 regarding TPOAb and TgAb positivity ( P = 0.004, 0.003). After adjustment, the RCS analysis detected nonlinear associations between iron and TPOAb and TgAb positivity ( P < 0.01, both). In stratified analyses, these associations regarding magnesium and iron remained for women of reproductive age, but not for postmenopausal women and men. We conclude that lower serum levels of magnesium and iron are associated with incremental positivity of thyroiditis antibodies and may be among the most important metals contributing to AIT in women of reproductive age.

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

Catalytic effect of cesium on the oxidation behavior of cation exchange resins in Li2CO3-Na2CO3-K2CO3 melt - Yang-Hai Zheng; Yong-De Yan; Yun Xue; Yue-Lin Wang; Xin Liu; Wan-Sheng Mi; Qing-Guo Zhang; Yu Li; Fu-Qiu Ma; Mi-Lin Zhang; Zhi-Hao Gan; Kai Zhu (Environmental Science and Pollution Research, 2022)

Effects of soil organic matter components and iron aluminum oxides on aggregate stability during vegetation succession in granite red soil eroded areas - Zhe Lin; Zhi-gang Huang; Da-lan Liao; Wan-xia Huang; Juan Huang; Yu-song Deng (Journal of Mountain Science, 2022)

Plant secondary metabolite and temperature determine the prevalence of Arsenophonus endosymbionts in aphid populations - Chun‐Yan Chang; Xiao‐Wan Sun; Pan‐Pan Tian; Ning‐Hui Miao; Yu‐Lin Zhang; Xiang‐Dong Liu (Environmental Microbiology, 2022)
Summary Transmission rate and role in hosts contribute to the prevalence of an endosymbiont. However, factors affecting transmission and role of facultative endosymbionts are still not well understood. Here, we illustrated that host plants and environmental temperatures affected the transmission, relative abundance and role of Arsenophonus in the cotton aphid Aphis gossypii . The transmission rate of this endosymbiont from mother aphids to offspring was relatively lower. High temperatures impeded the transmission, and infection rates declined as aphids were exposed to 30°C. Contents of amino acids and secondary metabolites were remarkably different among host plants. Aphids feeding on zucchini leaves containing a higher titre of amino acids and lower secondary metabolites harboured a relatively lower abundance of Arsenophonus . Concentrations of an amino acid and a plant secondary metabolite, cucurbitacin B, in aphid diet were not associated with Arsenophonus abundance. However, gossypol, another plant secondary metabolite, was strongly related with the abundance. Arsenophonus imparted a fitness benefit to aphids, and the benefit was dependent on host plants and gossypol concentration. In sum, plant secondary metabolite and environmental temperature affect transmission, relative abundance and role of Arsenophonus , which determine the endosymbiont prevalence in aphid populations.

Fissistiganoids A and B: two new flavonoids from the Fissistigma tungfangense - Wan-Lin Zhong; Xue-Ming Zhou; Ji-Ling Yi; Xin-Ming Song; Bin Zhang; Jing-Yu Yang; Guang-Ying Chen (Natural Product Research, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Development of novel polymorphic microsatellite markers for Picea brachytyla - Shuai-Peng Si; Chun-Jing Wang; Ji-Zhong Wan; Yu-Lin Qian; Chun-Hui Zhang (Molecular Biology Reports, 2022)

Effects of Involuntary and Voluntary Exercise in Combination with Acousto-Optic Stimulation on Adult Neurogenesis in an Alzheimer's Mouse Model - Wan-yi Li; Jun-yan Gao; Su-Yang Lin; Shao-tao Pan; Biao Xiao; Yu-tao Ma; Kai Xie; Wei Shen; Zhi-tao Liu; Guang-yu Li; Jie-jie Guo; Qin-wen Wang; et al. (Molecular Neurobiology, 2022)

Hippocampal SIRT1-Mediated Synaptic Plasticity and Glutamatergic Neuronal Excitability Are Involved in Prolonged Cognitive Dysfunction of Neonatal Rats Exposed to Propofol - Lin-Hui Ma; Jie Wan; Jing Yan; Ning Wang; Yan-Ping Liu; Hai-Bi Wang; Cheng-Hua Zhou; Yu-Qing Wu (Molecular Neurobiology, 2022)

Detection of pulmonary tuberculosis in children using the Xpert MTB/RIF Ultra assay on sputum: a multicenter study - Xiaoshan Peng; Qiong Liao; Min Fang; Yu Zhu; Yan Shi; Shuting Quan; Yacui Wang; Li Duan; Xiaomei Shi; Yang Liu; Manzhi Wang; Qingsong Wei; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

The Effects of Limosilactobacillus reuteri LR-99 Supplementation on Body Mass Index, Social Communication, Fine Motor Function, and Gut Microbiome Composition in Individuals with Prader–Willi Syndrome: a Randomized Double-Blinded Placebo-Controlled Trial - Xue-Jun Kong; Kevin Liu; Patrick Zhuang; Ruiyi Tian; Siyu Liu; Cullen Clairmont; Xiaojing Lin; Hannah Sherman; Junli Zhu; Yelan Wang; Michelle Fong; Alice Li; et al. (Probiotics and Antimicrobial Proteins, 2021)
Prader–Willi syndrome (PWS) is a rare genetic disorder associated with developmental delay, obesity, and neuropsychiatric comorbidities. Limosilactobacillus reuteri ( Lactobacillus reuteri , Lact. reuteri ) has demonstrated anti-obesity and anti-inflammatory effects in previous studies. In the present study, we aim to evaluate the effects of Lact. reuteri supplementation on body mass index (BMI), social behaviors, and gut microbiota in individuals with PWS. We conducted a 12-week, randomized, double-blind, placebo-controlled trial in 71 individuals with PWS aged 6 to 264 months (64.4 ± 51.0 months). Participants were randomly assigned to either receive daily Lact. reuteri LR-99 probiotic (6 × 10 10 colony forming units) or a placebo sachet. Groupwise differences were assessed for BMI, ASQ-3, and GARS-3 at baseline, 6 weeks, and 12 weeks into treatment. Gut microbiome data was analyzed with the QIIME2 software package, and predictive functional profiling was conducted with PICRUSt-2. We found a significant reduction in BMI for the probiotic group at both 6 weeks and 12 weeks relative to the baseline ( P < 0.05). Furthermore, we observed a significant improvement in social communication and interaction, fine motor function, and total ASQ-3 score in the probiotics group compared to the placebo group ( P < 0.05). Altered gut microbiota was observed in the probiotic group to favor weight loss and improve gut health. The findings suggest a novel therapeutic potential for Lact. reuteri LR-99 probiotic to modulate BMI, social behaviors, and gut microbiota in Prader–Willi syndrome patients, although further investigation is warranted. Trial registration Chinese Clinical Trial Registry: ChiCTR1900022646

The Decision Strategies of Adolescents with Different Emotional Stabilities in Unfair Situations - Yajing Si; Lin Jiang; Chanlin Yi; Qi Zhang; Cunbo Li; Jing Yu; Peiyang Li; Qiang Liu; Feng Wan; Fali Li; Dezhong Yao; Peng Xu (Neuroscience Bulletin, 2021)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Prenylated xanthones and biphenyls from Garcinia esculenta with antistaphylococcal activity - Dan Zheng; Hong Zhang; Jia-Ming Jiang; Yu-Yu Chen; Shi-Jie Wan; Zhi-Xiu Lin; Hong-Xi Xu (Natural Product Research, 2021)

Detection of Vestibular Schwannoma on Triple-parametric Magnetic Resonance Images Using Convolutional Neural Networks - Tzu-Hsuan Huang; Wei-Kai Lee; Chih-Chun Wu; Cheng-Chia Lee; Chia-Feng Lu; Huai-Che Yang; Chun-Yi Lin; Wen-Yuh Chung; Po-Shan Wang; Yen-Ling Chen; Hsiu-Mei Wu; Wan-You Guo; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose The first step in typical treatment of vestibular schwannoma (VS) is to localize the tumor region, which is time-consuming and subjective because it relies on repeatedly reviewing different parametric magnetic resonance (MR) images. A reliable, automatic VS detection method can streamline the process. Methods A convolutional neural network architecture, namely YOLO-v2 with a residual network as a backbone, was used to detect VS tumors from MR images. To heighten performance, T1-weighted–contrast-enhanced, T2-weighted, and T1-weighted images were combined into triple-channel images for feature learning. The triple-channel images were cropped into three sizes to serve as input images of YOLO-v2. The VS detection effectiveness levels were evaluated for two backbone residual networks that downsampled the inputs by 16 and 32. Results The results demonstrated the VS detection capability of YOLO-v2 with a residual network as a backbone model. The average precision was 0.7953 for a model with 416 × 416-pixel input images and 16 instances of downsampling, when both the thresholds of confidence score and intersection-over-union were set to 0.5. In addition, under an appropriate threshold of confidence score, a high average precision, namely 0.8171, was attained by using a model with 448 × 448-pixel input images and 16 instances of downsampling. Conclusion We demonstrated successful VS tumor detection by using a YOLO-v2 with a residual network as a backbone model on resized triple-parametric MR images. The results indicated the influence of image size, downsampling strategy, and confidence score threshold on VS tumor detection.

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Germination dynamics of allergenic fungal spores in respiratory mucus - Wan-Rou Lin; Szu-Yu Chen; Shih-Ching Hsiao; Pi-Han Wang (Aerobiologia, 2021)

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Western North Pacific Tropical Cyclone Database Created by the China Meteorological Administration - Xiaoqin Lu; Hui Yu; Ming Ying; Bingke Zhao; Shuai Zhang; Limin Lin; Lina Bai; Rijin Wan (Advances in Atmospheric Sciences, 2021)
This paper describes the access to, and the content, characteristics, and potential applications of the tropical cyclone (TC) database that is maintained and actively developed by the China Meteorological Administration, with the aim of facilitating its use in scientific research and operational services. This database records data relating to all TCs that have passed through the western North Pacific (WNP) and South China Sea (SCS) since 1949. TC data collection has expanded over recent decades via continuous TC monitoring using remote sensing and specialized field detection techniques, allowing collation of a multi-source TC database for the WNP and SCS that covers a long period, with wide coverage and many observational elements. This database now comprises a wide variety of information related to TCs, such as historical or real-time locations (i.e., best track and landfall), intensity, dynamic and thermal structures, wind strengths, precipitation amounts, and frequency. This database will support ongoing research into the processes and patterns associated with TC climatic activity and TC forecasting.

Heterosis-associated genes confer high yield in super hybrid rice - Tianzi Lin; Cong Zhou; Gaoming Chen; Jun Yu; Wei Wu; Yuwei Ge; Xiaolan Liu; Jin Li; Xingzhou Jiang; Weijie Tang; Yunlu Tian; Zhigang Zhao; et al. (Theoretical and Applied Genetics, 2020)
Key message Heterosis QTLs, including qSS7 and qHD8, with dominance effects were identified through GBS and large-scale phenotyping of CSSLs and hybrid F 1 populations in a paddy field. Abstract Heterosis has contributed immensely to agricultural production, but its genetic basis is unclear. We evaluated dominance effects by creating two hybrid populations: a B-homo set with a homozygous background and heterozygous chromosomal segments and a B-heter set with a heterozygous background and homozygous segments. This was achieved by crossing a set of 156 backcrossed-derived chromosome segment substitution lines (CSSLs) with their recurrent parent (9311), the male parent of the first super-high-yield hybrid Liangyoupei9 (LYP9), and with the female parent (PA64s) of the hybrid. The CSSLs were subjected to a genotyping-by-sequencing analysis to develop a genetic map of segments introduced from the PA64s. We evaluated the heterotic effects on eight yield-related traits in the hybrid variety and F 1 populations in large-scale field experiments over 2 years. Using a linkage map consisting of high-density SNPs, we identified heterosis-associated genes in LYP9. Five candidate genes contributed to the high yield of LYP9, with qSS7 and qHD8 repeatedly detected in both B-hybrid populations. The heterozygous segments harboring qSS7 and qHD8 showed dominance effects that contributed to the heterosis of yield components in the hybrid rice variety Liangyoupei9.

Effects of high-intensity interval training on gut microbiota profiles in 12 months’ old ICR mice - Guiping Wang; Huanhuan Zhou; Lin Zhang; Ruyi Li; Li Luo; Zengli Yu; Zhongxiao Wan (Journal of Physiology and Biochemistry, 2020)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Multiple genetic factors affecting the pharmacokinetic and pharmacodynamic processes of tacrolimus in Chinese myasthenia gravis patients - Huan-Yu Meng; Xi Li; Wan-Lin Jin; Cheng-Kai Yan; Xiao-Hua Dong; Qiu Xu; Yu-Yao Peng; Zhi-Bin Li; Yi Li; Zhao-Hui Luo; Li-Qun Xu; Huan Yang (European Journal of Clinical Pharmacology, 2020)

Effects of Elevated Ozone Concentrations on Root Characteristics and Soil Properties of Elaeocarpus sylvestris and Michelia chapensis - Lan Pan; Wan-qi Lin; Ming Yu; Gan-wen Lie; Li Xue; Hong-yue Chen (Bulletin of Environmental Contamination and Toxicology, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Profiling the microbial contamination in aviation fuel from an airport - Dong Hu; Wenfang Lin; Jie Zeng; Peng Wu; Menglu Zhang; Lizheng Guo; Chengsong Ye; Kun Wan; Xin Yu (Biofouling, 2019)

Interpreting air temperature generated from urban climatic map by urban morphology in Taipei - Yu-Cheng Chen; Tzu-Wen Lo; Wan-Yu Shih; Tzu-Ping Lin (Theoretical and Applied Climatology, 2019)

Thymosin Alpha-1 Inhibits Complete Freund’s Adjuvant-Induced Pain and Production of Microglia-Mediated Pro-inflammatory Cytokines in Spinal Cord - Yunlong Xu; Yanjun Jiang; Lin Wang; Jiahua Huang; Junmao Wen; Hang Lv; Xiaoli Wu; Chaofan Wan; Chuanxin Yu; Wenjie Zhang; Jiaying Zhao; Yinqi Zhou; et al. (Neuroscience Bulletin, 2019)

The analgesic effect and possible mechanisms by which koumine alters type II collagen-induced arthritis in rats - Gui-Lin Jin; Jian Yang; Wan-Qing Chen; Jie Wang; Hong-Qiang Qiu; Ying Xu; Chang-Xi Yu (Journal of Natural Medicines, 2019)

The influences of industrial gross domestic product, urbanization rate, environmental investment, and coal consumption on industrial air pollutant emission in China - Wei-yu Zhou; Wen-lin Yang; Wen-xin Wan; Jing Zhang; Wei Zhou; Hao-shen Yang; Hua Yang; Hong Xiao; Shi-huai Deng; Fei Shen; Ying-jun Wang (Environmental and Ecological Statistics, 2018)

Detection, sequence analysis, and antibody prevalence of porcine deltacoronavirus in Taiwan - Tien-Huan Hsu; Hao-Ping Liu; Chieh-Yu Chin; Chinling Wang; Wan-Zhen Zhu; Bing-Lin Wu; Yu-Chung Chang (Archives of Virology, 2018)

Association Between Body Mass Index and Disease Severity in Chinese Spinocerebellar Ataxia Type 3 Patients - Jin-Shan Yang; Ping-Ping Chen; Min-Ting Lin; Mei-Zhen Qian; Hui-Xia Lin; Xiao-Ping Chen; Xian-Jin Shang; Dan-Ni Wang; Yu-Chao Chen; Bin Jiang; Yi-Jun Chen; Ning Wang; et al. (The Cerebellum, 2018)

Modeling and multi-objective optimization for ANAMMOX process under COD disturbance using hybrid intelligent algorithm - Bin Xie; Yong-wen Ma; Jin-quan Wan; Yan Wang; Zhi-cheng Yan; Lin Liu; Ze-yu Guan (Environmental Science and Pollution Research, 2018)

Variations of Laohugou Glacier No. 12 in the western Qilian Mountains, China, from 1957 to 2015 - Yu-shuo Liu; Xiang Qin; Ji-zu Chen; Zhen-lin Li; Jing Wang; Wen-tao Du; Wan-qin Guo (Journal of Mountain Science, 2018)

Associations of rs3740677 within GAB2 Gene with LOAD in Chinese Han Population - Jing-Yu Zheng; Hui-Fu Wang; Yu Wan; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Effects of HLA-DRB1/DQB1 Genetic Variants on Neuroimaging in Healthy, Mild Cognitive Impairment, and Alzheimer’s Disease Cohorts - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Jinyuan Liu; Yu Wan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Genetic Association of HLA Gene Variants with MRI Brain Structure in Alzheimer’s Disease - Zi-Xuan Wang; Yu Wan; Lin Tan; Jinyuan Liu; Hui-Fu Wang; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

PGRN Is Associated with Late-Onset Alzheimer’s Disease: a Case–Control Replication Study and Meta-analysis - Hui-Min Xu; Lin Tan; Yu Wan; Meng-Shan Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

A Missense Variant in TREML2 Reduces Risk of Alzheimer’s Disease in a Han Chinese Population - Teng Jiang; Yu Wan; Jun-Shan Zhou; Meng-Shan Tan; Qing Huang; Xi-Chen Zhu; Huan Lu; Hui-Fu Wang; Qi Chen; Lin Tan; Ying-Dong Zhang; Lan Tan; et al. (Molecular Neurobiology, 2017)

Impacts of sediment type on the performance and composition of submerged macrophyte communities - Lin Liu; Xiang-Qi Bu; Jun-Yan Wan; Bi-Cheng Dong; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Aquatic Ecology, 2017)

The catalytic subunit of magnesium-protoporphyrin IX monomethyl ester cyclase forms a chloroplast complex to regulate chlorophyll biosynthesis in rice - Weiyi Kong; Xiaowen Yu; Haiyuan Chen; Linglong Liu; Yanjia Xiao; Yunlong Wang; Chaolong Wang; Yun Lin; Yang Yu; Chunming Wang; Ling Jiang; Huqu Zhai; et al. (Plant Molecular Biology, 2016)

Pollen and seed flow under different predominant winds in wind-pollinated and wind-dispersed species Engelhardia roxburghiana - Zheng-Feng Wang; Ju-Yu Lian; Wan-Hui Ye; Hong-Lin Cao; Qian-Mei Zhang; Zhang-Ming Wang (Tree Genetics & Genomes, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Tumor MICA status predicts the efficacy of immunotherapy with cytokine-induced killer cells for patients with gastric cancer - Yu Chen; Wan-song Lin; Wei-feng Zhu; Jing Lin; Zhi-feng Zhou; Chuan-zhong Huang; Gang Chen; Yi Shi; Zeng-qing Guo; Yun-bin Ye (Immunologic Research, 2016)

Allyl isothiocyanate (AITC) inhibits pregnane X receptor (PXR) and constitutive androstane receptor (CAR) activation and protects against acetaminophen- and amiodarone-induced cytotoxicity - Yun-Ping Lim; Ching-Hao Cheng; Wei-Cheng Chen; Shih-Yu Chang; Dong-Zong Hung; Jih-Jung Chen; Lei Wan; Wei-Chih Ma; Yu-Hsien Lin; Cing-Yu Chen; Tsuyoshi Yokoi; Miki Nakajima; et al. (Archives of Toxicology, 2015)

Permian ultrafelsic A-type granite from Besar Islands group, Johor, peninsular Malaysia - Azman A Ghani; Fatin Izzani Hazad; Azmiah Jamil; Quek Long Xiang; Wan Nur Atiqah Wan Ismail; Sun-Lin Chung; Yu-Ming Lai; Muhammad Hatta Roselee; Nur Islami; Kyaw Kyaw Nyein; Meor Hakif Amir Hassan; Mohd Farid Abu Bakar; et al. (Journal of Earth System Science, 2014)

Genetic diversity and identification of race 3 of Fusarium oxysporum f. sp. lactucae in Taiwan - Ying-Hong Lin; Po-Jung Lai; Tao-Ho Chang; Yu-Ling Wan; Jenn-Wen Huang; Jin-Hsing Huang; Pi-Fang Linda Chang (European Journal of Plant Pathology, 2014)

Association Study Between Macrophage Migration Inhibitory Factor-173 Polymorphism and Acute Myeloid Leukemia in Taiwan - Latha Ramireddy; Chien-Yu Lin; Su-Ching Liu; Wan-Yu Lo; Rouh-Mei Hu; Yi-Chin Peng; Ching-Tien Peng (Cell Biochemistry and Biophysics, 2014)

Novel quasi-subgenotype D2 of hepatitis B virus identified in Taiwanese aborigines - Huy Tran; Ming-Lung Yu; Chia-Yen Dai; I-Ling Lin; Ming-Lun Yeh; Wan-Long Chuang; Kenji Abe (Virus Genes, 2014)

Differential expression of speckled POZ protein, SPOP: Putative regulation by miR-145 - Chiu-Jung Huang; Hsing-Yu Chen; Wan-Yi Lin; Kong Bung Choo (Journal of Biosciences, 2014)

γ-Aminobutyric acid (GABA) homeostasis regulates pollen germination and polarized growth in Picea wilsonii - Yu Ling; Tong Chen; Yanping Jing; Lusheng Fan; Yinglang Wan; Jinxing Lin (Planta, 2013)

Application of a web-based remote agro-ecological monitoring system for observing spatial distribution and dynamics of Bactrocera dorsalis in fruit orchards - Joe-Air Jiang; Tzu-Shiang Lin; En-Cheng Yang; Chwan-Lu Tseng; Chia-Pang Chen; Chung-Wei Yen; Xiang-Yao Zheng; Chun-Yi Liu; Ren-Hau Liu; Yu-Fan Chen; Wan-Yi Chang; Cheng-Long Chuang (Precision Agriculture, 2013)

Effectiveness of participatory training for prevention of musculoskeletal disorders: a randomized controlled trial - Wenzhou Yu; Ignatius T. S. Yu; Xiaorong Wang; Zhimin Li; Sabrina Wan; Hong Qiu; Hui Lin; Shaohua Xie; Trevor Sun (International Archives of Occupational and Environmental Health, 2013)

Hyperinakin, a new anti-inflammatory phloroglucinol derivative from Hypericum nakamurai - Yuan-Bin Cheng; Ahmed Eid Fazary; Yu-Chi Lin; I-Wen Lo; Seow-Chin Ong; Shun-Ying Chen; Ching-Te Chien; Yen-Jung Lin; Wan-Wan Lin; Ya-Ching Shen (Natural Product Research, 2013)

hPNAS-4 inhibits proliferation through S phase arrest and apoptosis: underlying action mechanism in ovarian cancer cells - Lei Li; Den-bang Chen; Chao Lin; Kang Cao; Yang Wan; Xin-yu Zhao; Chun-lai Nie; Zhu Yuan; Yu-quan Wei (Apoptosis, 2013)

Albumin prevents reactive oxygen species-induced mitochondrial damage, autophagy, and apoptosis during serum starvation - Shu-Yu Liu; Chia-Ling Chen; Tsan-Tzu Yang; Wei-Ching Huang; Chia-Yuan Hsieh; Wan-Jou Shen; Tsung-Ting Tsai; Chi-Chang Shieh; Chiou-Feng Lin (Apoptosis, 2012)

Idebenone inhibition of glutamate release from rat cerebral cortex nerve endings by suppression of voltage-dependent calcium influx and protein kinase A - Yi Chang; Yu-Wan Lin; Su-Jane Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

A hybrid strategy to integrate surface-based and mutual-information-based methods for co-registering brain SPECT and MR images - Yuan-Lin Liao; Yung-Nien Sun; Wan-Yuo Guo; Yuan-Hwa Chou; Jen-Chuen Hsieh; Yu-Te Wu (Medical & Biological Engineering & Computing, 2011)

Change of air quality and its impact on atmospheric visibility in central-western Pearl River Delta - Jun-Ming Wan; Mang Lin; Chuen-Yu Chan; Zhi-Sheng Zhang; Guenter Engling; Xue-Mei Wang; Iat-Neng Chan; Shi-Yu Li (Environmental Monitoring and Assessment, 2011)

Isolation of new esters from the stems of Cinnamomum reticulatum Hay - Iung-Jr Lin; Wen-Li Lo; Yi-Chen Chia; Lee-Yu Huang; Thau-Ming Cham; Wan-Shan Tseng; Yu-Ting Yeh; Hung-Chun Yeh; Yau-Der Wang; Chung-Yi Chen (Natural Product Research, 2010)

Registration of Micro-Computed Tomography and Histological Images of the Guinea Pig Cochlea to Construct an Ear Model Using an Iterative Closest Point Algorithm - Chia-Fone Lee; Gen-Jia Li; Shu-Yen Wan; Wen-Jeng Lee; Kai-Yuan Tzen; Chiung-Hsiang Chen; Yu-Lin Song; Yuan-Fang Chou; Yuh-Shyang Chen; Tien-Chen Liu (Annals of Biomedical Engineering, 2010)

Isolation and characterization of microsatellites in Chinese white olive (Canarium album) and cross-species amplification in Canarium pimela - Xin Zhang; Wan-Hui Ye; Hong-Lin Cao; Zheng-Feng Wang; Hao Shen; Ju-Yu Lian (Conservation Genetics, 2009)

KIFC1 participates in acrosomal biogenesis, with discussion of its importance for the perforatorium in the Chinese mitten crab Eriocheir sinensis - Keming Yu; Lin Hou; Jun-Quan Zhu; Xue-Ping Ying; Wan-Xi Yang (Cell and Tissue Research, 2009)

Deletion analysis of the C-terminal region of a molecular chaperone DnaK from Bacillus licheniformis - Wan-Chi Liang; Min-Guan Lin; Meng-Chun Chi; Hui-Yu Hu; Huei-Fen Lo; Hui-Ping Chang; Long-Liu Lin (Archives of Microbiology, 2009)

Analysis of the mechanisms underlying the endothelium-dependent antivasoconstriction of puerarin in rat aorta - Li-Ping Yan; Yu-Lan Zhuang; Shun-Wan Chan; Shi-Lin Chen; Gang-Gang Shi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Interaction between SARS-CoV helicase and a multifunctional cellular protein (Ddx5) revealed by yeast and mammalian cell two-hybrid systems - Jin-Yan Chen; Wan-Nan Chen; Kwok-Man Vincent Poon; Bo-Jian Zheng; Xu Lin; Yong-Xiang Wang; Yu-Mei Wen (Archives of Virology, 2009)

Eighteen novel polymorphic microsatellite loci developed from the Père David’s deer (Elaphurus davidianus) - Hai-Long Wu; Xiao-Wei Ni; Lin-Yuan Zhang; Jin-Shi Xia; Zhen-Yu Zhong; Guo-Ping Zhu; Qiu-Hong Wan (Conservation Genetics, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Mutation analysis of 218 Chinese patients with Wilson disease revealed no correlation between the canine copper toxicosis gene MURR1 and Wilson disease - Zhi-Ying Wu; Gui-Xian Zhao; Wan-Jin Chen; Ning Wang; Bo Wan; Min-Ting Lin; Shen-Xing Murong; Long Yu (Journal of Molecular Medicine, 2006)

Grassland degradation in Northern Tibet based on remote sensing data - Qingzhu Gao; Yu’e Li; Yunfan Wan; Erda Lin; Wei Xiong; Wangzha Jiangcun; Baoshan Wang; Wenfu Li (Journal of Geographical Sciences, 2006)

Stabilization of a truncated Bacillus sp. strain TS-23 α-amylase by replacing histidine-436 with aspartate - Huei-Fen Lo; Ya-Hui Chen; Nai-Wan Hsiao; Hsiang-Ling Chen; Hui-Yu Hu; Wen-Hwei Hsu; Long-Liu Lin (World Journal of Microbiology and Biotechnology, 2005)

Transgenic tomato plants expressing the Arabidopsis NPR1 gene display enhanced resistance to a spectrum of fungal and bacterial diseases - Wan-Chi Lin; Ching-Fang Lu; Jia-Wei Wu; Ming-Lung Cheng; Yu-Mei Lin; Ning-Sun Yang; Lowell Black; Sylvia K. Green; Jaw-Fen Wang; Chiu-Ping Cheng (Transgenic Research, 2004)